Plantar Pressure Variation during Jogging with Different Heel Height - Y. D. Gu; D. Sun; J. S. Li; M. R. Graham; X. J. Ren (Applied Bionics and Biomechanics)
This paper presents the key testing and analysis results of an investigation on the effect of heel height on the plantar pressure over different foot areas in jogging. It is important in improving the understanding of jogging with high heels and damage/injury prevention. It can also potentially guide the development of suitable/adaptive exercise schemes in between daily activities with high heels. In this work, plantar pressure data were collected from 10 habituated healthy female subjects (aged 21–25 years) at their natural jogging speed with three different conditions: flat heeled shoes (0.8 cm), low heeled shoes (4.0 cm), and high heeled shoes (6.6 cm). Data analysis showed significantly differences in plantar pressure distribution associated with the heel heights with increased pressure in the first metatarsal region and decreased pressure in the lateral metatarsal and midfoot sections. However, there is no significant alteration of plantar pressure in the central area of the forefoot with jogging gait.